International Experience in Adult Education: Transformation of Institutional Forms - Maksim Yu. Semenov; Marina N. Kicherova; Irina S. Trifonova (National Research Mordova State University, 2024)
Introduction. The article is devoted to the problem of institutional boundaries blurring triggered by the disintegration of traditional institutions, the emergence of new educational formats. The aim is to institutionally analyse the international experience in adult education, explore traditional and new forms, and identify key vectors of change. Materials and Methods. The methodological framework is an ecosystem approach, comparative, institutional and thematic content analyses of scientific publications. In the first step, the authors analysed statistical data and identified three groups of countries according to the level of adult involvement in lifelong learning. In the second step, the authors conducted a socio-historical review of institutional forms of adult education in different countries. Results. The analytical review allowed the authors to identify traditional and new institutional forms, as well as their representation in different countries. It was proved that traditional institutions are being replaced by new formats due to the development of digital technologies and the EdTech industry. Traditional institutions are characterized by internal stability, clear boundaries and hierarchy. They are being replaced by flexible, hybrid institutional structures based on digital communication networks with horizontal links. Roles and statuses of participants in the learning process, instructional design, learning pathways, procedures, assessment technologies, which are the key vectors of institutional transformation, have changed. Discussion and Conclusion. Having analysed historical experience and international best practices in adult education, the authors substantiate a possible evolutionary scenario of institutional changes. The results obtained contribute to the development of scientific ideas about the relationship between the labour market, EdTech industry and institutional forms in adult education to synchronize supply and demand. The study can be used to develop social policy measures for training different population groups and create a national ecosystem of lifelong adult education.